2003
DOI: 10.1093/emboj/cdg390
|View full text |Cite
|
Sign up to set email alerts
|

Activation of phospholipase D by the small GTPase Sar1p is required to support COPII assembly and ER export

Abstract: The small GTPase Sar1p controls the assembly of the cytosolic COPII coat that mediates export from the endoplasmic reticulum (ER). Here we demonstrate that phospholipase D (PLD) activation is required to support COPII‐mediated ER export. PLD activity by itself does not lead to the recruitment of COPII to the membranes or ER export. However, PLD activity is required to support Sar1p‐dependent membrane tubulation, the subsequent Sar1p‐dependent recruitment of Sec23/24 and Sec13/31 COPII complexes to ER export si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
61
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 41 publications
6
61
0
Order By: Relevance
“…S2-S4), leading to functional ERES assembly (Figs 5,7). The results support a model in which regulatory activities such as lipid signaling (Blumental-Perry et al, 2006;Farhan et al, 2008;Nagaya et al, 2002;Pathre et al, 2003) control the progression of a molecular cascade that directs COPII nucleation and activity at ERES (Fig. 8).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…S2-S4), leading to functional ERES assembly (Figs 5,7). The results support a model in which regulatory activities such as lipid signaling (Blumental-Perry et al, 2006;Farhan et al, 2008;Nagaya et al, 2002;Pathre et al, 2003) control the progression of a molecular cascade that directs COPII nucleation and activity at ERES (Fig. 8).…”
Section: Discussionsupporting
confidence: 82%
“…p125A or SNX9 were depleted by immunoprecipitation from RLC. The resulting supernatants were adjusted for protein concentration, verified for similar Sec23 and HSP70 levels, and used to measure COPII recruitment to microsomes as described previously (Pathre et al, 2003).…”
Section: Coat Recruitment To Luvs or Er Microsomesmentioning
confidence: 99%
“…Thus, the interaction we describe here provides a potential mechanism for integrating the requirements for COPII binding, protein phosphorylation and 14-3-3 recruitment at a single intracellular location. This notion of COPII acting as a platform for the recruitment of the necessary machinery molecules to ERES is consistent with the long-lived nature of ERES (Hammond and Glick, 2000;Stephens, 2003;Stephens et al, 2000) and the fact that COPII can recruit other machinery molecules such as SNARES (Mossessova et al, 2003), phospholipases (Pathre et al, 2003) and motor protein complexes (Watson et al, 2005).…”
Section: Discussionsupporting
confidence: 75%
“…PLD1 also appears to participate in anterograde transport 27 and is activated by ARF1. Overexpression of PLD1 gave rise to small but statistically significant increases in the secretion of both VLDL 1 and VLDL 2, confirming our results in a cell-free system, 12 which suggested that PLD is important for the second step of VLDL assembly.…”
Section: Discussionmentioning
confidence: 99%